Re-conceptualizing the Construction of Political Education for Women's Party Cadres Based on Gender Competences and Needs - Al Rafni; Suryanef Suryanef; Cici Nur Azizah (Indonesian Research Journal in Education |IRJE|, 2022)
Political education for women cadres is a primary concern for the low quality (performance) of women's politics in the public world. Especially, for women’s party cadres, it is necessary to reconstruct the conception of political education so that occurs in politics. Researchers also targeted 45 informants from academics, practitioners, and the party's women cadres. The method used is a grounded theory approach to obtain field data as the basis for theory construction/conceptualization of the resulting theory. The research results indicated that the reconceptualization of the political education construction must be carried out on a philosophical, juridical, sociological, and practical basis. Three things that need to be reconceptualised, which are (1) the meaning of the essence of political education; (2) the process of implementing political education; and (3) the competencies that must be possessed by women’s party cadres. Recommendations are also discussed for political parties, government, and women political groups.